Pre-Islamic Arab Societies: Uncovering Cultural Heritage, Social Systems, and Belief Systems - Moh. Nor Ichwan (RaSAIL Media Group, Semarang, Indonesia, 2024)
Pre-Islamic Arab society is a social group that inhabited the Arab region before the advent of Islam. Their rich culture, social structures, and belief systems have contributed significantly to the Middle East's historical advancement and civilization. This article seeks to provide a fuller understanding of pre-Islamic Arab society by emphasizing some aspects of the predominant cultural, social, and religious systems at the time. This study uses literary analysis to consult historical sources like ancient writings, trip diaries, and archaeological artefacts. A historical study has also been done to compile precise and comprehensive data. The research findings show pre-Islamic Arab society had a diverse and rich culture. They developed the highly respected Arabic language, poetry, and literary traditions. Their social structure comprises tribes, and each tribe has its strict hierarchy and moral laws. However, the variety of their religious traditions includes monotheistic, animism, polytheism, and paganism. This article argues that pre-Islamic Arab societies had a complex and rich cultural heritage. Their belief system incorporates numerous forms of mysticism, and their social order is founded on a solid tribal structure. Grasp pre-Islamic Arab society in depth can help one understand the Middle East region's history and culture.